Impact of host and histopathological factors on the discrepancies in estrogen receptor, and progesterone receptor, and HER2 status between core needle biopsy and surgically excised tumors. (April 2016) - Nakamura, Rikiya; Yamamoto, Naohito; Shiina, Nobumitsu; Miyaki, Toshiko; Ikebe, Dai; Itami, Makiko; Shida, Takashi; Miyazaki, Masaru
Abstract: Purpose: The high reliability and utility of core needle biopsy (CNB) have been previously described. Our aim in this study was to clarify the host and histopathological factors influencing the discrepancies in ER, PgR, and HER2 status between CNB and surgically excised tumors (SET). Methods: All patients diagnosed with operable invasive breast cancer in our hospital between January 2005 and April 2015 were included in the study; patients who required neoadjuvant chemotherapy were excluded. ER, PgR, and HER2 expression were assessed between paired CNB and SET samples. ER and PgR status were determined using immunohistochemistry(IHC). HER2 status was determined using IHC and scored from 0 to 3+. Fluorescence in-situ hybridization analysis was carried out in HER2 2+ cases. The cut off point for ER and PgR positivity was set at 1%. Results: A total of 1307 patients were assessed. The concordance rates of ER, PgR, and HER2 status in CNB and SET were 95%, 84% and 97%, respectively. Factors of discrepancy were nuclear grade, histological type, and menopausal status for ER and PgR, and none detected for HER2. The discrepancy factors were assessed with univariate and multivariate analysis. Conclusions: Using the largest known dataset to date of paired samples from a single institution, we evaluated the accuracy of CNB and the discrepancy factors between CNB and SET in breast cancer patients. We conclude that CNB for ER and PgR assessment in postmenopausal patients before treatment should be used with caution. Further research will contribute to increased CNB accuracy, improving patient treatment decisions. Highlights: This study is one of the largest published data series to investigate ER, PgR, and HER2 status. There was a high concordance rate between CNB and the surgical specimen. This concordance rate was associated with the clinical characteristics of the patient. The accuracy of CNB has decreased owing to the change in the cut-off point of positive ER and PgR. The outcomes of the discordance group in ER+ and PgR+ cases were poor.